Hydrophobically modified low molecular weight chitosan for drug delivery / Tiew Shu Xian - Tiew, Shu Xian (2018)
Hydrophobically modified chitosan which are able to self-aggregate as a hydrophobic core and a hydrophilic corona architecture in an aqueous physiological environment are drawing attention and developing tremendously in drug delivery due to their numerous advantages and biological potentials. In this study, 25 kDa low molecular weight chitosan (Ch3) was prepared via depolymerization with nitrous acid for better solubility and introduced with different chain lengths of hydrophobic alkyl groups to obtain butyryl (ChC4), hexanoyl (ChC6), octanoyl (ChC8), decanoyl (ChC10) and lauryl chitosan (ChC12) for the evaluation as drug carriers. The successful acylation of the alkyl chain was confirmed via fourier-transform infrared (FTIR), 1H and 13C nuclear magnetic resonance (NMR) analyses, as well as the change in zeta potential to a negative value after acylation. The water solubility, critical aggregation concentration and particle size were greatly influenced by the alkyl chain length and degree of substitution (DS) of acylated low molecular weight chitosan (ChA). Thermogravimetric analysis (TGA), X-ray diffraction (XRD) and viscosity showed the effect of acylation to the hydrogen bonding of the chitosan. Observations from both transmission electron microscope (TEM) and field-emission scanning electron microscope (FE-SEM) showed that ChA formed spherical particles, in which longer chain acylated chitosan have larger particle size due to possible larger occupancy volume. The encapsulation of ChA with four model analgesic drugs of different solubilities including salicylic acid (SA), lidocaine (LID), acetaminophen (ACE) and caffeine (CAF), demonstrated that the encapsulation efficiency was dependent on the drug solubility and alkyl chain length. The particle size of ChA was larger after loading with slightly soluble drugs such as SA and LID compared to those of sparingly soluble drugs such as ACE and CAF. Additionally, the size increment was more pronounced in short alkyl chain acylated chitosan (ChC4 and ChC6) with higher rigidity. The morphology from TEM micrographs showed that ChA maintained their spherical shape after drug loading. The in vitro drug release from ChA in phosphate buffer saline pH 7.4 for topical delivery using inline vertical Franz diffusion cells and in simulated gastric fluid (SGF) pH 1.2 for oral delivery using dialysis tubing demonstrated that ChA were able to slow down the release of free drug solutions by following the Korsmeyer-Peppas model, where both swelling and diffusion were involved in the release mechanism. The hydrophobically modified low molecular weight chitosan were promising carriers to prolong drug release, with lauryl chitosan showing the best drug sustainability among the ChA.